Spinal cord injury: global burden from 1990 to 2019 and projections up to 2030 using Bayesian age-period-cohort analysis - Liu, Yanbo; Yang, Xuesong; He, Zhigang; Li, Juan; Li, Yijing; Wu, Yanqiong; Manyande, Anne; Feng, Maohui; Xiang, Hongbing (Frontiers in Neurology, 2023)
Background Spinal cord injuries, often resulting from spine fractures, can lead to severe lifelong symptoms such as paraplegia and even mortality. Over the past few decades, there has been a concerning increase in the annual incidence and mortality rates of spinal cord injuries, which has also placed a growing financial strain on healthcare systems. This review aims to offer a comprehensive overview of spinal cord injuries by estimating their global incidence, prevalence, and the impact in terms of years lived with disability, using data obtained from the 2019 Global Burden of Disease Study. Method In this study, we utilized data from the 2019 Global Burden of Disease Study, a widely recognized source for global health data. Our methodology involved estimating the global incidence and prevalence of spinal cord injuries while also assessing the impact on years lived with a disability. We analyzed this data comprehensively to identify patterns and trends and made predictions. Finding This research delved into the evolving trends in the global burden of spinal cord injuries, identified key risk factors, and examined variations in incidence and disability across different Socio-demographic Index (SDI) levels and age groups. Briefly, in 2019, the global incidence and burden of YLDs of SCI significantly increased compared to 1990. While males had higher incidence rates compared to females. Falls were identified as the primary cause of SCI. Trend projections up to 2030 revealed a slight decrease in ASIR for males, an upward trend in age-specific incidence rates for both sexes and a similar pattern in age-standardized YLD rates. Additionally, our findings provided crucial groundwork for shaping future policies and healthcare initiatives, with the goal of mitigating the burden of spinal cord injuries, enhancing patient outcomes, and fortifying prevention efforts. Interpretation Understanding the global burden of spinal cord injuries is essential for designing effective healthcare policies and prevention strategies. With the alarming increase in prevalence rates and their significant impact on individuals and healthcare systems, this research contributes vital insights to guide future efforts in reducing the incidence of spinal cord injuries, improving the quality of life for affected individuals, and reducing the economic burden on healthcare systems worldwide.